Kedudukan Jaksa Selaku Pelaksana Mewakili Negara Dalam Sistem Peradilan Pidana - Adriansya Mukhtar; Ma'ruf Hafidz; Muhammad Fachri Said (Journal of Lex Generalis (JLG), 2022)
Tujuan penelitian menganalisis kedudukan jaksa selaku pelaksana mewakili negara dalam sistem peradilan pidana dan independesi jaksa selaku pelaksana mewakili negara dalam sistem peradilan pidana. Metode Penelitian ini adalah penelitian hukum normatif. Hasil penelitian bahwa (1) Kedudukan dan peran Kejaksaan Republik Indonesia dalam sistem pemerintahan telah ditegaskan dalam penjelasan UUD 1945 dan Undang-Undang Nomr 16 Tahun 2004 tentang Kejaksaaan Republik Indonesia yang menyatakan bahwa kedudukan kejaksaan adalah lembaga pemerintahan yang melaksanakan kekuasaan negara terutama dibandingkan penuntutan di lingkungan peradilan umum. (2) Pelaksanaan fungsi kejaksaan dalam melaksanakan tugas dan wewenangnya Kejaksaan membina hubungan kerjasama dengan badan penegak hukum dan keadilan serta badan negara atau instansi lain. The research objective to analyze the position of the prosecutor as the executor of representing the state in the criminal justice system and the independence of the prosecutor as the executor of representing the state in the criminal justice system. Methods This research is a normative legal research. The results of the study are that (1) The position and role of the Prosecutor's Office of the Republic of Indonesia in the government system has been confirmed in the explanation of the 1945 Constitution and Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia which states that the position of the Prosecutor's Office is a government institution that exercises state power, especially compared to prosecution in the environment. general court. (2) Implementation of the function of the public prosecutor's office in carrying out its duties and authorities. The Prosecutor's Office maintains cooperative relations with law and justice enforcement agencies and state agencies or other agencies.